Evidence for Lattice Strain and Non-ideal Behavior in the (La1−xEux)PO4 Solid Solution from X-ray Diffraction and Vibrational Spectroscopy - Geisler, Thorsten; Popa, Karin; Konings, Rudy J. M. (Frontiers in Earth Science, 2016)
The monazite-type solid solution of LaPO$_4$ and EuPO$_4$ has been studied by X-ray diffraction, infrared (IR) and Raman spectroscopic techniques. A substantial excess molar volume has been derived from the X-ray data, and the Raman and IR spectra show band broadening typical for mixing of cations of different size on the cation sublattice. The IR spectra were interpreted by the autocorrelation method and the excess autocorrelation parameter $Δ{corr}^{ex}$ shows clear deviation from ideal solution behaviour, similar to the observed broadening of the Raman bands. The results can be interpreted in terms of local lattice strains resulting from the ion size effects of substitution of La$^{3+}$ by Eu$^{3+}$, and correlate very well with calorimetric measurements of the excess enthalpy that was previously measured.